The influence of motor skills on the short sprint results - Nikola Aksović; Iryna Skrypchenko; Bojan Bjelica; R. Ram Mohan Singh; Filip Milanovic; Dejan Nikolic; Milan Zelenović (IP Iermakov S.S., 2021)
Background and Study Aim. The curriculum of physical education in high schools is based on learning motor skills, as well as their development in sports sections, where the 100-meter sprint dominates. The aim of the study was to determine the influence of motor skills on the 100 m running results. Material and Methods. The research was conducted on a sample of 80 high school students in Novi Pazar and Kraljevo, aged 16 and 17 years (± 6 months). 12 variables were used to assess motor skills, three variables each: explosive power, segmental speed, repetitive power, and flexibility (standing long jump), triple jump, five jumps. For estimating segmental speed: foot tapping, hand tapping, foot tapping on the wall. For the assessment of repetitive power: lifting the torso on the Swedish bench, mixed pull-ups, squats. To assess flexibility: deep bench press, twine, stick twist. Results. Results were obtained to confirm that there is a positive influence of motor skills on the 100 m sprint results at the level of (p=.000). The results in the 100 m sprints are statistically significantly dependent on the motor skills that manifest segmental speed and explosive power. Variables (standing long jump, foot tapping on the wall and foot tapping) have a statistically significant effect on the criterion variable of the 100 m sprint. Conclusions. Recommendation to future researchers would be to conduct a study over a longer period of time with the aim of examining the biomechanical factors that determine the success in sprint, is the production of force in the phase of sprint acceleration and sprint deceleration.